2011
DOI: 10.1142/s0217751x11051573
|View full text |Cite
|
Sign up to set email alerts
|

The EFFECTS OF a FAMILY NONUNIVERSAL Z′ BOSON ON B → Ππ DECAYS

Abstract: Motivated by the measured large branching ratio ofB 0 → π 0 π 0 (the so-called "ππ" puzzle), we investigate the effects of a family non-universal Z ′ model on the tree-dominated B → ππ decays. We find that the Z ′ coupling parameter ζ LR d ∼ 0.05 with a nontrivial new weak phase φ L d ∼ −50 • , which is relevant to the Z ′ contributions to the QCD penguin sector △C 5 , is needed to reconcile the observed discrepancy. Combined with the recent fitting results from B → πK, πK * and ρK decays, the Z ′ parameter sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 135 publications
0
3
0
Order By: Relevance
“…Similar with the ππ, πK or ρρ puzzles discussed in Refs. [84,[95][96][97][98][99][100][101][102], the B → πρ puzzle has been noticed by some groups [103][104][105][106][107][108][109]. For example, in Ref.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…Similar with the ππ, πK or ρρ puzzles discussed in Refs. [84,[95][96][97][98][99][100][101][102], the B → πρ puzzle has been noticed by some groups [103][104][105][106][107][108][109]. For example, in Ref.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…It has been shown that models with an additional neutral gauge boson, so-called Z 0 models, not only explain ϵ 0 =ϵ [28][29][30][31][32][33], but also provide a promising solution to the B → Kπ puzzle [34][35][36][37][38][39][40], since they affect electroweak penguin operators [41,42]. Furthermore, the anomalies in b → sl þ l − data [43][44][45][46][47][48][49][50], which, using a global fit, convincingly point towards NP [51][52][53][54][55][56][57][58][59][60], can be explained within Z 0 models .…”
Section: Introductionmentioning
confidence: 99%
“…[45,46] were also investigated in the same framework. The effects of the family non-universal Z gauge boson are also searched for in B → ππ decays in [47]. Recently, the B 0 s − B0 s mixing, B → K * l + l − , B s → μ + μ − , B → Kπ and inclusive B → X s l + l − decays have been analyzed and stronger constraints have been placed on the family non-universal Z model parameters in [48][49][50][51][52] (see also [33,34]).…”
Section: Introductionmentioning
confidence: 99%